2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.23505
|View full text |Cite
|
Sign up to set email alerts
|

African American Women in the Academe: A Comprehensive Literature Review Through the Lens of Intersectionality

Abstract: A first year Engineering Education doctoral student at Purdue University. Ms. Trina L Fletcher, Purdue University, West LafayetteTrina Fletcher is an Engineering Education doctoral student at Purdue University. Her research focus includes process excellence and total quality management (TQM) methodologies as a way to improve engineering related activities within industry and education. She is also interested in research around recruiting and retaining underrepresented minorities and women in STEM. Prior to Pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…Additionally, the findings from other studies report that BWEF tend to encounter unique challenges along the tenure track [3], and have high extended family responsibility [1]. These factors can contribute to a lower self-efficacy, which correlates to feelings of institutional fit [3]. On the other hand, perceptions of institutional fit can also be positively influenced by mentoring.…”
Section: Constructs Overviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, the findings from other studies report that BWEF tend to encounter unique challenges along the tenure track [3], and have high extended family responsibility [1]. These factors can contribute to a lower self-efficacy, which correlates to feelings of institutional fit [3]. On the other hand, perceptions of institutional fit can also be positively influenced by mentoring.…”
Section: Constructs Overviewmentioning
confidence: 99%
“…Some of the personal attributes of BWEF influence the experiences they have in the workplace and their career outcomes. Studies have shown that BWEF experience slightly higher stress than other faculty [2,3]. Time constraints on completing activities, promotion concerns, and variations in expectations contribute to these higher stress levels; this is particularly true for women of color at four-year colleges [3].…”
Section: Constructs Overviewmentioning
confidence: 99%
See 3 more Smart Citations